IMPROVING ENGLISH IMPLICIT GRAMMAR KNOWLEDGE USING SEMANTICO-SYNTACTIC TRANSLATION PRACTICE - Futuh Handoyo (TEFLIN Journal: A publication on the teaching and learning of English, 2010)
Abstract: The present was to respond to the studentsâ low implicit grammar knowledge and, therefore, was concerned with its improvement. The subjects of the study were twenty six students of the first semester accounting students of State Polytechnic of Malang. The strategy used was semantico-syntactic translation practice, which proceeded through three main stages: upgrading their explicit grammar knowledge followed by internalizing the knowledge into explicit grammar knowledge, and testing the result. The result showed that the determined goal was reached in fifteen meetings within one cycle with some extra meetings for oral internalization practice.